Personal Data-Smart Cities: How cities can Utilise their Citizen's Personal Data to Help them Become Climate Neutral - Topham, Shaun; Boscolo, Paolo; Mulquin, Michael (Taylor & Francis, 2023)
This book sets out to address some of the issues that a smart city needs to overcome to make use of both the data currently available to them and how this can be enhanced by using emerging technology enabling a citizen to share their personal data, adding value. It provides answers for those within a smart city, advising their mayors or leaders on introducing new technology. We will cover the topic so as to enable many different public officials to be able to understand the situation from their own perspective, be they lawyers, financial people, service providers, those looking at governance structures, policy makers, etc. We are contributing to the new model for the European Data Economy. Case studies of existing best practice in the use of data are augmented with examples of embracing a citizen's personal data in the mix, to enable better services to develop and potential new revenue streams to occur. This will enable new business models and investment opportunities to emerge. We will address the topic of how to put a value on data and will conclude by looking at what new technologies will be emerging in the coming years, to help cities with carbon-neutral targets to have more chance of succeeding.